The Regulation of Screening of Foreign Direct Investments in the European Union- Key Features and Reaches - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The subject of analysis in this paper are the key features of the regulatory concept of Foreign Direct Investment Screening established by Regulation 2019/452. The rules of the said Regulation are directed towards three main pillars, which simultaneously define its essence. First, it establishes the position of Member States and their national screening mechanisms, imposing requirements and obligations that these mechanisms must observe; second, it provides a list of factors that Member States’ screening authorities may take into account when evaluating investments; and third, it authorizes the European Commission to issue opinions on specific foreign direct investments. Based on this analysis, the scope of the legal framework of the Regulation is determined. In terms of content, Regulation 2019/452 creates a flexible and conceptually incomplete framework, the key determinants of which are essentially defined by the distribution of powers and factual influence between EU Member States and the European Commission, as well as by the list of factors defining the subject of protection. As a novelty in EU law, it represented a conceptual step forward providing concrete benefits. However, overall, the results of its framework are highly questionable. It essentially fails to achieve either the objectives of the Regulation itself or to satisfy the specific interests involved in this field. Therefore, significant changes to the regulation of this area at the EU level are necessary in the near future, aimed at creating a more concrete, precise, and efficient regulation.